A comparative performance analysis of three standardized climatic drought indices in the Chi River basin, Thailand - Homdee, Tipaporn; Pongput, Kobkiat; Kanae, Shinjiro (Agriculture and Natural Resources, 2016)
Drought indices are generally used as a tool for monitoring changes in drought conditions. This paper evaluated the performance of three climatic drought indices to characterize drought trends in the Chi River basin in Northeast Thailand. Initially, the drought assessment was conducted using the Standardized Precipitation Index (SPI), a precipitation-based index, and the Standardized Precipitation Evapotranspiration Index (SPEI), an index taking into account the difference between precipitation and potential evapotranspiration (PET). Then, this study simply applied an index called the Standardized Precipitation Actual Evapotranspiration Index (SPAEI), similar to the commonly used SPEI, with the difference being in the use of actual evapotranspiration (AET) instead of PET. Time series of the three indices were compared with observed droughts. The results indicated that various indicators of different indices can have diverse effects on drought conditions. The simple SPI, considering only precipitation, can be used to identify characteristics of droughts with certain restrictions. Being multivariate indices, the SPEI and the SPAEI were able to clearly detect the temporal variability of droughts to a greater extent than the SPI index. Moreover, the different results derived from using P-AET instead of P-PET made a substantial difference to temporal drought severity. Thus, climatic water demand had important aspects in determining the drought conditions for this area.